Salmon fisheries in Ireland and the report of the Irish Inland Fisheries Commission - Conner, H. D. (Statistical and Social Inquiry Society of Ireland, 1906)
The object of this paper is to bring before this Society the importance of the salmon fishery to the country districts of Ireland, to give an outline of the conditions essential to insure its prosperity, and to summarize very shortly and necessarily inadequately the highly valuable report recently presented to the Lord Lieutenant by the Commission appointed to inquire into the state of the Inland Fisheries of Ireland, and presided over by Lord Justice Walker. Now, in reference to the importance of the salmon fishery in country districts, it is a trite and hackneyed remark, which probably has been many times repeated in this room, that the fact that Ireland is not, and possibly can never be, a manufacturing country on a large scale, makes it all the more vital that every nerve should be strained to develop any natural advantages that the country possesses, and to encourage wealthy Englishmen to come to this country, and to spend in it their superfluous riches, which they are only" too anxious to do, on the mere condition that they can be assured of a moderate amount of really good sport. Now, I believe that, taking it all round, good salmon fishing on a river in Ireland causes an expenditure of money in the district, which to anyone, except an ardent fisherman, appears quite out of propoition to the actual number of fish brought to bank by the fishing tenant, and further that this expenditure benefits a number of persons, and is distributed in directions that renders it even more valuable than that which takes place in other branches of sport, or in the ordinary tourist traffic.
Read Friday, 17th May, 1901
Keywords: Salmon fishing, Ireland; Conservation, Fish stocks, Ireland; Fisheries, Ireland; Irish Inland Fisheries Commission; 314.15